Spray drying of lipid-based systems loaded with Camellia sinensis polyphenols. (2nd January 2017) - Secolin, Vanessa A.; Souza, Claudia R. F.; Oliveira, Wanderley P.
Abstract: In this work, spray-dried lipid systems based on soy phosphatidylcholine, cholesterol and lauroyl polyoxylglycerides for entrapping Green tea polyphenols were produced. The aim was to study the effects of the encapsulating composition and spray drying conditions on the system performance and physicochemical product properties. The spray dryer powder production yield falls around 50.7 ± 2.8%, which is typical for lab scale spray dryers. Wrinkled and rounded particles, with low surface porosities were generated, independent of the drying carriers (trehalose or lactose) used. The product showed high encapsulation efficiency of Green tea polyphenols, which was promptly redispersible in water. It presented low density, and good compressive and flow properties. The results herein reported confirm the feasibility of the entrapment of Green tea polyphenols in lipid-based compositions by spray drying in presence of the drying carriers evaluated. The spray-dried microparticles show high potential to be used as additive in food, nutraceutical and pharmaceutical products.